Культурно-образовательная среда вуза - Мардахаев, Л.В. (My University, 2013)
Cultural and educational environment of the university is, the current socio-cultural environment in time serving necessary necessary condition and a factor in the system of vocational education, which determines the student's identity in it and shaping it as a specialist.